Relationship between merging lane length and motorcyclist’s head check behavior during merging in expressway - Ammar, Adnan; H., Ismail; Radin Umar, Radin Zaid; S., Samuel; Shaffiar, Norhashimah; Mohd Hanafi, Ani; Abdul Hamid, Abd. Malek (Publications International Lahore, Pakistan, 2018)
In Malaysia, risky driving/riding is accounted for two-thirds of the total road crashes. It includes speeding, ignoring signal or sign, improper overtaking and merging. In this study, the focus is on motorcyclist's behavior during merging in traffic. The objectives are: (i) to evaluate motorcyclist’s head check behavior during merging in urban expressway; and (ii) to evaluate the effect of merging lane length on motorcyclist’s head check behavior during merging in traffic – urban expressway. Field observational study was conducted at 16 scenario locations with different lengths of merging lane (20 – 300 meters). The recording was done for 4 weeks on 1600 motorcyclists. Each scenario was observed from 2.00 p.m. to 5.00 p.m. on a good weather condition. Dependent variable of the study is the percentage of head check. If a motorcyclist performed head check towards the target zone while in launch zone, he or she was scored 1, otherwise 0 (binary scoring). Results obtained shows that, three-quarters (76.9%) of the motorcyclists did not performed head check during merging onto urban expressway. Among regression models being analyzed, cubic regression model shows the highest correlation value, R2 of 0.644. Merging lanes between 147 – 227 meters was found to be the optimal length that may influence the motorcyclists to perform head check during merging in traffic. Findings from this study, recommended the merging road design improvement for road safety. In addition, it contributes in improving the riding education program in general, specifically on how to merge safely during merging in traffic.